The nature of some nonlinear optic coefficients in ferroelectrics - Chew, Khian Hooi; Tilley, D.R.; Webb, J.F.; Osman, J. (2001)
Nonlinear optic coefficients that have been calculated through the resonant region in the far-infrared are looked at. It is possible to make such calculations by using a systematic expansion based on the Landau-Devonshire expression for the free energy together with the Landau-Khalatnikov dynamical equations. In this paper the coefficients considered have been calculated for an isotropic paraelectric phase. Two third order examples are presented: third harmonic generation and the d.c. Kerr effect. Experimental and practical implications include those for far-infrared sources and Terrahertz wave technology.